Processes and Features of Subsidence Dolines (Sinkholes) - Veress, Márton (Global Journal of Earth Science and Engineering, 2022)
This study deals with the processes of subsidence dolines. These processes contribute to the understanding of the characteristics of karst areas and the relation between dolines and their environment. For this, several hundred dolines of various karst areas were studied. Investigations included measurements of doline size and processes (for example mass movements), the mapping of their morphology and processes, observation and tracking of some processes (for instance water inflow). Laboratory experiments were carried out, and we had VES measurements performed to obtain data on their sediments. The processes of dolines with various development phase were distinguished. The processes of developed dolines were classified according the site of their effect which may be present in the environment, on the side slope, on the floor, on the cover below the floor and in the bedrock. The processes were also put into groups based on their direction. It was established that the degree of supplier and transporting away processes and their value compared to each other controls doline size, while the denudation of the doline slope and the accumulation on its floor influences doline shape.